Development of Detection Instrument Models for Mobility Impairment in The Older Adults Based on A Mobile Health Nursing Application in A Public Health Center - Riksa Wibawa Resna; Lutfan Lazuardi; Sri Werdati; Wasilah Rochmah (Jurnal Ners, 2019)
Introduction: Mobility impairment is a problem in the older adults who have decreased in mobility as it may affect their daily activity. The development of a detection model to identify the problem of mobility impairment in older adults has become a solution that can increase the health care for older adults. This study aimed to develop a health detection instrument models using a mobile health nursing application to detect mobility impairment in older adults.Methods: This study used action research through a purposive sampling method involving three nurses and twenty-seven cadres to perform the detection process of mobility impairment focused on one hundred and seventy-five older adults in three public health centers in two provinces using an m-health application.Results: Based on direct observation and questionnaires addressed to the user of the m-health nursing application, 80% stated that the information contained in the mobile health nursing application was appropriate. In terms of speed, only 43.33% stated that the application worked fast, but overall, 66.67% of users stated that they were delighted with the application-based of the instrument model and that they were helped in detecting the mobility disorders that occurred in the older adults.Conclusion: These applications can be developed into a model that can help nurses, older adults and their family to detect other older adult problems in addition to mobility problems like cognitive function etc.